CHRONIC GROIN PAIN FOLLOWING INGUINAL HERNIA REPAIR IN THE LAPAROSCOPIC ERA: A SYSTEMATIC REVIEW - Oky Firmansyah, Muhammad; Nabila Almansyuri, Intan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage. Chronic pain is any pain which persists beyond the normal healing period of 12 weeks. Postherniorrhaphy groin pain is defined as pain lasting >3 months after surgery, which is one of the most important complications occurring after inguinal hernia repair, and occurs with greater frequency than previously thought. The aim: This study aims to show chronic groin pain following inguinal hernia repair in the laparoscopic era. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 103 articles, whereas the results of our search on SagePub brought up 113 articles. The results of the search conducted for the last year of 2013 yielded a total 80 articles for PubMed and 49 articles for SagePub. The result from title screening, a total 14 articles for PubMed and 8 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Chronic pain following inguinal hernia repair causes significant morbidity to patients and should not be ignored. Preemptive analgesia and operation under local anesthesia significantly affect pain. Intraoperative identification and preservation of all inguinal nerves are very important. Early diagnosis and management of chronic pain can remove suffering of the patient.